PROCESS APPROACH TO THE DECOMPOSITION OF THE TRANSPORTATION PROCESS OF THE CARRIAGE OF CARGO BY MARITIME TRANSPORT - Коскіна, Юлія Олексіївна (Science-based technologies, 2019)
The process of cargo transportation by maritime transport using the process approach which allows to structure the process into separate components, setting the beginning and end of the process, the resources of the process and to identify the owners of the transportation process. The object of transportation is cargo, and the result of the transportation process — the change of cargo’s state in time and in geographical space. The owners of the cargo transportation process set to be the buyer and/or seller of the goods — within their responsibility (in accordance with the terms of delivery of cargo under the purchase contract) for the organization of transportation of cargo to a named geographical point within a certain time. Transportation of goods by sea is a set of processes of the individual participants of carriage, so the resources of the transportation process are defined as transport infrastructure (material) and document turnaround of the participants of the transportation of cargo by maritime transport (information resources). The vessel’s voyage on carrying the cargo from the port of loading to the port of discharging is one of the components of the cargo transportation process. The process approach allows to consider the vessel’s voyage to be a sub-process of the transportation process and in the same time — to search it as a separate one. The paper defines the result of the voyage (the movement of cargo between ports of loading and discharging) and the resources to reach the said result (material and information), the beginning and end of the voyage as vessel’s operating process. The feature with defining the owners of the searched process is emphasized in the paper: the sea carrier is responsible right for the direct movement of the cargo between ports of the voyage, while loading and discharging operations, both being the parts of the vessels voyage for sure, performs by stevedoring company and consider to be its own operating processes.